The Badshah Begums: Interrogating Identity and Power in Mughal Fictions - Kumari, Suman (Muslim English Literature, 2023)
The historical legacy of Mughal rule in India has never been devoid of the interplay of power politics and identity throughout its long history. Needless to say, the history of Mughal women abounds in instances of power struggle and hegemonic interplay of social position. This research paper intends to highlight Ira Mukhoty’s Daughters of the Sun and Indu Sundersan’s The Twentieth Wife, which explicitly throw light on this power exchange that inevitably occurred in the Mughal empire. The historical representation of Mughals has been surrounded by narratives of the central patriarchal seat of power. Besides, the paper intends to establish the dedication, intelligence, valor, and diplomacy of these Begums whose stories have never been part of the popular narrative. The catalytic role that these women played in building the Mughal empire, as Mukhoty says, needs to be studied as an essential aspect of the development of the Mughal kingdom in India. Considering popular theories of studying cultural theory, this paper questions the prevalent ideas of privilege, power, and position associated with the title of the Badshah Begum and reveals the true socio-cultural suppression that functioned in the background. This paper brings out how the Begums perceived the importance of the title themselves at the personal level, thus contributing to the growth of the domestic, economic, political, and academic levels.